Accessory Articulation of the Cervical Transverse Process: A Very Rare Anatomic Variant. Issue 1 (14th February 2018) - Braspenningx, Stéphanie; Simons, Philip
We present a very unusual case of an accessory articulation of the transverse processes of C6 and C7. Only four previous cases have been described in English literature. Our case stresses the importance of computed tomography (CT) and post-processing images to discriminate this variant from posttraumatic or degenerative lesions. Multiplanar reformations and volume-rendered images should be added to the cervical spine CT protocol.